Host-Parasite Interactions and Population Dynamics of Rock Ptarmigan. - Ute Stenkewitz; Ólafur K Nielsen; Karl Skírnisson; Gunnar Stefánsson (PLOS ONE, 2016)
Populations of rock ptarmigan (Lagopus muta) in Iceland fluctuate in multiannual cycles with peak numbers c. every 10 years. We studied the ptarmigan-parasite community and how parasites relate to ptarmigan age, body condition, and population density. We collected 632 ptarmigan in northeast Iceland in early October from 2006 to 2012; 630 (99.7%) were infected with at least one parasite species, 616 (98%) with ectoparasites, and 536 (85%) with endoparasites. We analysed indices for the combined parasite community (16 species) and known pathogenic parasites, two coccidian protozoans Eimeria muta and Eimeria rjupa, two nematodes Capillaria caudinflata and Trichostrongylus tenuis, one chewing louse Amyrsidea lagopi, and one skin mite Metamicrolichus islandicus. Juveniles overall had more ectoparasites than adults, but endoparasite levels were similar in both groups. Ptarmigan population density was associated with endoparasites, and in particular prevalence of the coccidian parasite Eimeria muta. Annual aggregation level of this eimerid fluctuated inversely with prevalence, with lows at prevalence peak and vice versa. Both prevalence and aggregation of E. muta tracked ptarmigan population density with a 1.5 year time lag. The time lag could be explained by the host specificity of this eimerid, host density dependent shedding of oocysts, and their persistence in the environment from one year to the next. Ptarmigan body condition was negatively associated with E. muta prevalence, an indication of their pathogenicity, and this eimerid was also positively associated with ptarmigan mortality and marginally inversely with fecundity. There were also significant associations between fecundity and chewing louse Amyrsidea lagopi prevalence (negative), excess juvenile mortality and nematode Capillaria caudinflata prevalence (positive), and adult mortality and skin mite Metamicrolichus islandicus prevalence (negative). Though this study is correlational, it provides strong evidence that E. muta through time-lag in prevalence ...